Understanding Generation Z's Intentions To Apply For Jobs Through Employer Attractiveness, Corporate Reputation, and Social Media - Maulinda, Liestya Dwi; Aryati, Ana Sofia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The fierce